Standardization and Quality Evaluation of Duck Meat Sausages - Naveen, Z.; Reddy, S.K. Gurunatha; Rao, B. Eswara; Reddy , P.M. (Journal of Meat Science, 2015)
Four trials were conducted for standardization of duck meat sausage recipe. In each trial, six desi ducks were slaughtered, dressed conventionally and chilled to an internal temperature of 4±1°C. Out of six dressed duck carcasses, three were deboned manually after partial cooking and remaining deboned without cooking. The partially cooked and raw boneless duck meats were used separately for further processing and development of an ideal recipe. The de-boned meats were minced and mixed with different levels of binders (by replacing 5% and 10% of meat with bengal gram flour (BGF) and soya bean flour (SBF) separately), other ground seasonings and condiments to obtain a uniform batter. The sausages were evaluated for cooking loss, emulsion stability, moisture, crude protein and sensory evaluation. Duck meat sausages incorporated with SBF at 10% level had significantly (p
Keywords: Duck meat; Sausages; Cooking loss; Emulsion